2014
DOI: 10.1136/jech-2014-204186
|View full text |Cite
|
Sign up to set email alerts
|

Educational differences in mortality and the relative importance of different causes of death: a 7-year follow-up study of Spanish adults

Abstract: Although the causes of death with the strongest gradient in mortality rate are HIV disease in both sexes, diabetes mellitus in women and suicide in men, most of the absolute education-related inequalities in total mortality are due to cardiovascular diseases, respiratory diseases and diabetes mellitus in women and to cardiovascular diseases, respiratory diseases and cancer in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 35 publications
5
23
0
1
Order By: Relevance
“…This index has the advantage of providing a unique measure of the magnitude of inequality that can be compared across different countries, studies and diseases. 38 Our estimates of the RII are in line with that reported in a census-based Spanish study based on GC deaths registered between 2001 and 2008, 49 and with the results of the Turin Longitudinal study based on the Piedmont cancer registry collecting data between 1985 and 1999. 50 In these studies, the RII ranged between 1.96 in Spanish men and 3.24 in Italian men, that is, people in the highest rank of the socioeconomic hierarchy had a 30-50% reduction in GC mortality as compared to those in the lowest class.…”
Section: Discussionsupporting
confidence: 86%
“…This index has the advantage of providing a unique measure of the magnitude of inequality that can be compared across different countries, studies and diseases. 38 Our estimates of the RII are in line with that reported in a census-based Spanish study based on GC deaths registered between 2001 and 2008, 49 and with the results of the Turin Longitudinal study based on the Piedmont cancer registry collecting data between 1985 and 1999. 50 In these studies, the RII ranged between 1.96 in Spanish men and 3.24 in Italian men, that is, people in the highest rank of the socioeconomic hierarchy had a 30-50% reduction in GC mortality as compared to those in the lowest class.…”
Section: Discussionsupporting
confidence: 86%
“…Among women, both absolute and relative inequalities in smoking-related deaths decreased over the study period while relative inequalities in lung cancer mortality were inexistent in 1971–1976, and tended to appear in favour of the less educated women over the end of the study period, probably as a consequence of increasing ASMR among the higher educational groups (see online supplementary figure S5). Results for lung cancer are in line with Italian findings of higher smoking rates among women with a high education at the beginning of the study period and among older women at the end of the study period,43 and are similar to those reported in a recent Spanish study 12. Decreasing absolute and relative inequalities in smoking-related mortality, on the other hand, may be explained by the fact that this category comprises heterogeneous causes of death which may be influenced by factors other than smoking.…”
Section: Discussionsupporting
confidence: 90%
“…Researchers have overcome this challenge by conducting (small area) ecological studies (Borrell and Arias 1995;Borrell et al 1997Borrell et al , 2010Esnaola et al 2006;Regidor et al 1995) and by performing linkage studies in local areas, such as Barcelona, Madrid, and the Basque country (Borrell et al 1999;Huisman et al 2004Huisman et al , 2005aMackenbach et al 2008;Puigpinós et al 2009). More recently, based on the 2001 census, Reques et al (2014) conducted a nationally representative follow-up study on individuals aged 25 and older during seven years and estimated mortality rates by education. Their results confirmed those from the earlier mentioned studies showing smaller educational mortality differences in Spain than in other countries in northern Europe.…”
Section: Differences In Longevitymentioning
confidence: 99%